Analysis of PBT and PET cyclic oligomers in extracts of coffee capsules and food simulants by a HPLC-UV/FLD method. (30th May 2021) - Alberto Lopes, Joao; Tsochatzis, Emmanouil D.; Karasek, Lubomir; Hoekstra, Eddo J.; Emons, Hendrik
Highlights: PET and PBT cyclic oligomers in food contact materials (plastic coffee capsules). Validation and application of a HPLC-UV/FLD for quantification of the studied PET and PBT oligomers. Method validation for 1st Series PET cyclic oligomers and PBT, with proper analytical standards, with known purity. Exposure assessment based on TTC and EFSA scientific opinions. Abstract: A HPLC-UV/FLD method was validated for the quantification of six polyethylene terephthalate (PET) and four polybutylene terephthalate (PBT) oligomers. PBT oligomers are EU regulated, while the PET ones are considered non-intentionally added substances (NIAS). LOQs were higher than 0.4 and 3.5 μg kg −1 for the simulants and in the polymer extracts, respectively. Recoveries ranged from 95 to 114 % with RSDs below 12%. Migration testing of PBT and polypropylene coffee capsules were performed with H2 O and simulant C, and extracts were obtained with accelerated solvent extraction (ASE). For the latter legislative limits weren't surpassed. As no migration limits are existing for the analytes, both EFSA's toxicological threshold of concern (TTC) and sum of oligomers approaches were applied. The majority of oligomers were below the TTC (90 µg/person/day), but the limit value of 50 µg/kg food was surpassed for some capsules, which indicates a significant intake in both single and multiple consumption.